Effectiveness of complementary pain treatment for women with deep endometriosis through Transcutaneous Electrical Nerve Stimulation (TENS): randomized controlled trial. (November 2015) - Mira, Ticiana A.A.; Giraldo, Paulo C.; Yela, Daniela A.; Benetti-Pinto, Cristina L.
Abstract: Objective: Evaluate TENS effectiveness as a complementary treatment of chronic pelvic pain and deep dyspareunia in women with deep endometriosis. Study design: This randomized controlled trial was performed in a tertiary health care center, including twenty-two women with deep endometriosis undergoing hormone therapy with persistent pelvic pain and/or deep dyspareunia. This study was registered in the Brazilian Record of Clinical Trials (ReBEC), under n RBR-3rndh6. TENS application for 8 weeks followed a randomized allocation into two groups: Group 1 – acupuncture-like TENS (Frequency: 8 Hz, pulse duration: 250 μs) – VIF ( n = 11) and Group 2 – self-applied TENS (Frequency: 85 Hz, pulse duration: 75 μs) ( n = 11). The intensity applied was "strong, but comfortable". We evaluated patients before and after treatment by the use of the Visual Analogue Scale, Deep Dyspareunia Scale and Endometriosis Quality of Life Questionnaire. We used the Wilcoxon and Mann–Whitney tests to compare before and after treatment conditions. Results: Despite the use of hormone therapy for 1.65 ± 2.08 years, the 22 women with deep endometriosis sustained pelvic pain complaints (VAS = 5.95 ± 2.13 and 2.45 ± 2.42, p < .001) and/or deep dyspareunia (DDS = 2.29 ± 0.46 and 1.20 ± 1.01, p = .001). We observed significant improvement for chronic pelvic pain, deep dyspareunia and quality of life by the use of TENS. Both application types of TENS were effective for improving the evaluated types of pain. Conclusions: Both resources (acupuncture-like TENS and self-applied TENS) demonstrated effectiveness as a complementary treatment of pelvic pain and deep dyspareunia, improving quality of life in women with deep endometriosis regardless of the device used for treatment.